2006
DOI: 10.1152/ajpcell.00401.2005
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box 1 protein interacts with multiple Toll-like receptors

Abstract: High mobility group box 1 (HMGB1), originally described as a DNA-binding protein, can also be released extracellularly and functions as a late mediator of inflammatory responses. Although recent reports have indicated that the receptor for advanced glycation end products (RAGE) as well as Toll-like receptor (TLR)2 and TLR4 are involved in cellular activation by HMGB1, there has been little evidence of direct association between HMGB1 and these receptors. To examine this issue, we used fluorescence resonance en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
611
4
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 812 publications
(635 citation statements)
references
References 46 publications
(64 reference statements)
15
611
4
5
Order By: Relevance
“…Several studies indicated that HMGB1 could interact with multiple receptors, including TLR2, TLR4, the receptor for advanced glycation end products, and, most recently, TLR9 (10,17,19,20,26). Similarly, varying intracellular signaling pathways, involving p38 MAP, ERK, JNK, and other kinases, were reported to be activated in HMGB1-exposed cells (10, 11, 19 -22, 27-32).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that HMGB1 could interact with multiple receptors, including TLR2, TLR4, the receptor for advanced glycation end products, and, most recently, TLR9 (10,17,19,20,26). Similarly, varying intracellular signaling pathways, involving p38 MAP, ERK, JNK, and other kinases, were reported to be activated in HMGB1-exposed cells (10, 11, 19 -22, 27-32).…”
Section: Discussionmentioning
confidence: 99%
“…29 The function of TLRs is not limited to pathogen control, and TLR2 and TLR4 have been implicated in wound healing in a noninfectious lung injury model. 38 In addition, TLR2 and TLR4 have not only been reported to recognize "stranger signals " from bacteria but also to transduce endogenous "danger signals " like fibronectin, 39 hyaluron acid, 40 and HMGB1, 41 all of which may be found at abundance within large areas of tissue necrosis in the setting of brain abscess. Thus, in our model, TLR2 and TLR4 might be required to limit the size and to resolve the abscess.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, dying cells release HMGB1 into the extracellular milieu in response to most chemotherapeutic agents (Apetoh et al, 2007a, b), and neutralization or depletion of HMGB1 abolishes the immunogenicity of cell death . HMGB1 can interact with several receptors expressed on the surface of DCs (Park et al, 2006) including tolllike receptor 4 (TLR4). Mice that lack TLR4 or that bear a mutant TLR4 fail to mount an immune response against anthracyclin-treated cancer cells .…”
Section: Introductionmentioning
confidence: 99%